A Review of Disputes in Claims for Loss and Expense Related to the PWD Form of Contract Based on Malaysian Legal Cases - Abdul Razak , Nurul Asyiqin; Ismail, Zulhabri; Brahim, Juliana (Journal of Technology Management and Business, 2023)
Construction disputes arising from claims have become common in this unique and complex industry. Resolving disputes leads to extra costs and is time-consuming. Most of the disputed claims in construction occur due to project delays. A claim for loss and expense is one of the claims incurred due to certain events that usually arise from the delay. Therefore, this paper aimed to identify disputes in claims for loss and expense related to the PWD form of contract based on Malaysian legal cases. Understanding why disputes occur in construction contracts can reduce the chances of their occurrence, and parties can establish a quick, cost-effective resolution process that will not jeopardise their potential in future business relationships when disputes arise. The research adopted a review related to construction law cases from 'Malayan Law Journal Report/Unreported'. Findings indicate that disputes in claims for loss and expenses related to the Public Works Department (PWD) form of contract can be categorised into contractual, documentation, and procedure. Understanding the contract provisions is a must for every construction party to obtain successful claims. This paper suggests identifying disputes related to PAM forms of contracts in the Malaysian construction industry, so that the contracting parties can understand the impact of the disputes.